(3dhYI GdTGci hOeYI GdHGcis ((3eMeO Hf EHQGgje GdbHGfi s)
(3ChdgG (B:s
(3hdGHO ef Tchi Edi Pi eQhAI jhGSjc Ch jSdjc Ch jJhLY CeG HYO MeO Gddg GdPi bVi HGdeMHI hGdhdhY aEffi CYQa ENhGfi Cf CVQ eG Ydi GdEfSGf ai cd ReGf , Cf jQNi WQag s
(3BNQgG (B:s
(3YSi GddjGdi CVfJ ef HaQbJfG MSHi SJLeYfi jhekG hJLeYg JeJ GdQSGdI s
(3HgG fXGe GdJYbjHIs
(3hgj ef cJH CHj aGQS CejQ GdeDefjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdCOHs